If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4a + -3b)(2a + 6b) = 0 Multiply (4a + -3b) * (2a + 6b) (4a * (2a + 6b) + -3b * (2a + 6b)) = 0 ((2a * 4a + 6b * 4a) + -3b * (2a + 6b)) = 0 Reorder the terms: ((24ab + 8a2) + -3b * (2a + 6b)) = 0 ((24ab + 8a2) + -3b * (2a + 6b)) = 0 (24ab + 8a2 + (2a * -3b + 6b * -3b)) = 0 (24ab + 8a2 + (-6ab + -18b2)) = 0 Reorder the terms: (24ab + -6ab + 8a2 + -18b2) = 0 Combine like terms: 24ab + -6ab = 18ab (18ab + 8a2 + -18b2) = 0 Solving 18ab + 8a2 + -18b2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '2'. 2(9ab + 4a2 + -9b2) = 0 Factor a trinomial. 2((4a + -3b)(a + 3b)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4a + -3b)' equal to zero and attempt to solve: Simplifying 4a + -3b = 0 Solving 4a + -3b = 0 Move all terms containing a to the left, all other terms to the right. Add '3b' to each side of the equation. 4a + -3b + 3b = 0 + 3b Combine like terms: -3b + 3b = 0 4a + 0 = 0 + 3b 4a = 0 + 3b Remove the zero: 4a = 3b Divide each side by '4'. a = 0.75b Simplifying a = 0.75bSubproblem 2
Set the factor '(a + 3b)' equal to zero and attempt to solve: Simplifying a + 3b = 0 Solving a + 3b = 0 Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. a + 3b + -3b = 0 + -3b Combine like terms: 3b + -3b = 0 a + 0 = 0 + -3b a = 0 + -3b Remove the zero: a = -3b Simplifying a = -3bSolution
a = {0.75b, -3b}
| 5xt-3xy= | | h(-0.5)=-4.5+3 | | y+.6=.8(y+2) | | y+.6=.8(y+2) | | Y=2b^2+4+9b | | [4x]=18+7y | | 2.3w+7+8.1+3w= | | 4.25*16= | | 10(2-m)-5(1-3m)=30 | | 0.53+0.34t=3.44t-0.71 | | 4y+16x=32 | | 0.53+0.34t=3.44t-0.71 | | 10(2-m)-5(1-3m)=30 | | 30+4n=95 | | 114=-6(2x-7) | | [7x-10]=X-6 | | 1.25+3y=7.25 | | -8(4m-6)=16(2m-5) | | 7x+3(4x-12)=154 | | -1(x+5)=3(x+9)-10 | | x+3(2x+4)=47 | | 3(2m-1)+m=m-3 | | 46+4x=-6x | | 8+3y=-7 | | findvc=kpv | | [5x+8]=x+12 | | 4(3m-5)-m=-m+16 | | (25)+(x+15)=(3x-10) | | Y=-0.414(70)+106.55 | | -1(x+m)=3(x+9)-10 | | 3x+-4=x+2 | | -85=5(1-3x) |